Efficacy of remimazolam versus midazolam for procedural sedation: post hoc integrated analyses of three phase 3 clinical trials - Dao, Van-Anh; Schippers, Frank; Stöhr, Thomas (Endoscopy International Open, 2022)
Background and study aims Remimazolam is an ultra-short acting, fast onset/fast offset benzodiazepine for intravenous use in procedural sedation, general anesthesia, and Intensive Care Unit sedation. The aim of this work was to compare the efficacy of remimazolam versus midazolam dosed according to medical practice (real-world midazolam) and midazolam dosed according to US prescribing information (on-label midazolam) for procedural sedation. Patients and methods This post hoc analysis was performed using integrated data from three randomized, placebo, and active (midazolam) controlled, phase 3 clinical trials in patients undergoing colonoscopy and bronchoscopy. Statistical comparisons between treatment groups, without adjustment for potential confounding factors, were exploratory and observational in nature.Results The mean ± SD dose of midazolam in the real-world midazolam group was 6.2 ± 3.1 mg, compared with 3.5 ± 1.5 mg in the on-label midazolam group. remimazolam showed significantly shorter time from first dose to start of procedure (median 3 minutes) compared to on-label midazolam (median 8 minutes). Recovery time from end of procedure to fully alert was significantly shorter for remimazolam (median 6 minutes) than real-world midazolam (median 14 minutes), enabling earlier transfer of patients from the procedure room to the recovery area with a lower requirement for patient monitoring. The onset and recovery times with remimazolam showed significantly less inter-patient variability than with on-label midazolam and real-world midazolam, respectively. Patients treated with remimazolam received significantly less fentanyl for analgesia (78.2 ± 28.4 µg) than did those treated with real-world midazolam (113.6 ± 60.1 µg) and on-label midazolam (92.5 ± 40.0 µg). Conclusions Remimazolam offers advantages over midazolam in terms of faster recovery and less fentanyl requirement, which may facilitate increased procedural throughput in clinical practice.